Trade Liberalization, Education, Inflation, FDI, and Urbanization: Implications for Income Inequality in the Developing World - Bashir, Furrukh; Munir, Farzana; Ali, Hina; Fatima, Syeda Neha (iRASD Journal of Economics, 2023)
The purpose of the present study is to analyze the influence of Trade openness, Expenditure in education, inflation, FDI, Household consumption expenditure, and urbanization on Income Inequality of some selected developing countries from 2006 to 2022. After collecting panel data of some selected developing economies from World Development Indicators, Im, Pesaran & Shin (IPS) – panel unit root test has been applied to check stationary levels of variables. Then, the panel ARDL technique was applied to the selected data after confirming the mixed order of integration (using IPS) of selected variables and the findings suggest that Income Inequality is significantly increased by Urbanization, Trade Openness, Inflation, and household consumption Expenditure while Expenditure in Education and Capital Formation significantly reduce Income Inequality in developing countries.